Yttrium-Doped \(γ\)-Glycine Crystals for Enhanced Nonlinear Optical Applications - M. Aynul Rifaya; G. Myvizhi; S. Malathi; V. Vijayalakshmi (Chemical and Materials Sciences: Research Findings Vol. 1, 2025)
The slow evaporation method was used to create the \(γ\)-glycine nonlinear optical (NLO) crystal at room temperature. The growing crystal belongs to the non-centrosymmetric space group P31 and has a hexagonal symmetric \(γ\)-polymorphic structure. According to the ICP-OES data, yttrium made up 0.025% of the 0.05% of the additional dopant. Linear optical transmittance studies were used to assess the impact of additives on the glycine crystal’s optical transparency. The crystal’s maximum linear optical transmittance was found to be 85%. The material’s thermal stability and possible polymorphic phase transitions were investigated using differential scanning calorimetry (DSC). The melting point of the grown crystal was observed at 256.8°C. It was discovered that the synthesized crystal’s second harmonic generation (SHG) efficiency was 3.5 times greater than the regular KDP crystals.